Enterprise Surveys : Nicaragua Country Profile 2010 - World Bank; International Finance Corporation (Washington, DC, 2014)
The enterprise surveys focus on the many factors that shape the business environment. The qualitative and quantitative data collected through the surveys connect a country s business environment characteristics with firm productivity and performance. The country profile for Nicaragua is based on data from the enterprise surveys conducted by the World Bank. The benchmarks include the averages for the group of countries in Latin America and Caribbean and the Nicaragua income group. The enterprise surveys collect a wide array of qualitative and quantitative information through face to face interviews with firm managers and owners regarding the business environment in their countries and the productivity of their firms. The topics covered in enterprise surveys include infrastructure, trade, finance, regulations, taxes and business licensing, corruption, crime and informality, finance, innovation, labor, and perceptions about obstacles to doing business.